Preparation method of flexible amino carbon nanotubes and BiOCl co-modified MXene sulfur-loaded cathode
Through the preparation method of co-modifying MXene sulfur-carrying cathode with flexible amino acid carbon nanotubes and BiOCl, the problems of poor conductivity and polysulfide shuttle effect of the cathode material of lithium sulfur batteries are solved, and better electrochemical performance and cyclic stability are achieved.
Patent Information
- Application Number
- CN202411845709.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The poor conductivity of sulfur, the shuttle effect of polysulfide, and the large volume expansion during deliquency/lithium embedding, lead to poor electrochemical performance.
The preparation method of co-modifying MXene sulfur-carrying cathode with flexible aminoamide carbon nanotubes and BiOCl is used to prepare the heterojunction structure material MXene-NH2CNT-BiOCl-x-S by ultrasonic assistance, and surface cation modification is used using CTAB to prevent MXene stacking and enhance conductivity.
The conductivity and cyclic performance of the cathode material of lithium sulfur batteries are improved, the adsorption capacity of polysulfides is enhanced, and the rate performance and capacity retention capacity of the battery are improved.
Smart Images

Figure CN119340326B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical energy storage secondary battery lithium sulfur battery, and specifically relates to a preparation method of a flexible amino carbon nanotube and BiOCl co-modified MXene sulfur-loaded positive electrode. Background Art
[0002] With the continuous development of social science and technology, people's demand for clean energy is becoming stronger and stronger. The commercialization of lithium-ion batteries (LIB) has greatly alleviated the problem of energy shortage, but it still has problems such as low battery capacity density and power density. Compared with LIB, lithium sulfur batteries (LSB) have a higher theoretical capacity (1675 mAh g -1 ) and energy density (2600 Wh kg -1 ). Nevertheless, LSB still faces many challenges, such as the poor conductivity of sulfur in the cathode material, the shuttling effect of polysulfides, and the large volume expansion during the de-lithiation / insertion process. Therefore, it is particularly important to develop electrode materials with good conductivity and inhibitory effect on the shuttling of polysulfides.
[0003] Excellent cathode materials play a vital role in the electrochemical performance of LSBs. In the past 20 years, researchers have mainly improved the performance of LSBs by looking for porous, stable and highly conductive sulfur host materials to load sulfur. Such host materials mainly include porous carbon, graphene, carbon nanotubes, carbon fibers and carbon materials derived from organic framework materials (biomass, MOFs and COFs, etc.). These host materials have a large specific surface area or a large internal cavity structure, high electronic conductivity and good chemical stability, which can alleviate the volume expansion of sulfur during charging and discharging, thereby improving the utilization of sulfur and inhibiting the shuttle effect of polysulfides.
[0004] MXene(Ti3C2T x) is a novel type of two-dimensional inorganic material. Few-layer MXene has a two-dimensional layered structure similar to graphene, with a high specific surface area, hydroxyl groups and terminal oxygen anion groups, so it has excellent metallic conductivity and hydrophilicity. However, few-layer MXene still has some defects: (1) Few-layer MXene is very easy to stack into multi-layer MXene again, which will greatly reduce the specific surface area of the material, greatly reduce the surface sites for sulfur binding, and reduce the utilization rate of sulfur. (2) Due to the large specific surface area, the surface of few-layer MXene is very easy to oxidize to form TiO2, which reduces the conductivity of MXene. Few-layer MXene has a short shelf life and requires a specific storage environment. Therefore, the excellent properties of few-layer MXene materials are used to prepare MXene-based heterojunction materials so that they can play their respective advantages and interact with each other, thereby preparing lithium-sulfur battery positive electrode materials with excellent electrochemical properties. Summary of the invention
[0005] In order to solve the above problems, the present invention proposes a method for preparing a MXene sulfur-loaded cathode co-modified with flexible amino carbon nanotubes and BiOCl.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The method for preparing a MXene sulfur-loaded cathode co-modified with flexible amino carbon nanotubes and BiOCl comprises the following steps: using a few-layer MXene as a substrate material, using a surfactant cetyltrimethylammonium bromide (CTAB) to perform surface cation modification on NH2CNT and BiOCl, preparing a heterojunction structure material MXene-NH2CNT-BiOCl-x (x=0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3 is the mass fraction of BiOCl) by ultrasound-assisted preparation, and then synthesizing a MXene-NH2CNT-BiOCl-xS material by an in-situ sulfur fixation method, the general formula of which is MXene-NH2CNT-BiOCl-xS (x=0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3), comprising the following steps:
[0008] S1. Preparation of multilayer MXene: Weigh 5-8 g lithium fluoride powder (LiF), dissolve it in a 50 mL polytetrafluoroethylene beaker containing 9-10 M hydrochloric acid and stir for 30-60 min. Slowly add 5-8 g MAX (Ti3AlC2) into the polytetrafluoroethylene beaker and stir for 20-24 h. Then centrifuge and wash with deionized water until the pH of the supernatant is >5. The precipitate obtained is multilayer MXene (Ti3C2T x ).
[0009] S2. Preparation of few-layer MXene: Pour a certain amount of anhydrous ethanol into a three-necked flask, pass inert gas for 10-15 minutes, then pour into a centrifuge tube containing multilayer MXene for ultrasonic centrifugation. After the centrifugation, pour out the supernatant. Pour deionized water from which air has been removed into a centrifuge tube containing the precipitate for ultrasonic centrifugation. After the centrifugation, the upper liquid obtained is the few-layer MXene. Use a filter membrane to filter a certain volume of the few-layer MXene, dry it, and weigh it to calculate the concentration of the few-layer MXene colloid.
[0010] S3. Preparation of BiOCl: Dissolve 5-8 mmol of bismuth nitrate pentahydrate (Bi(NO3)2·5H2O) in 10 mL of ethylene glycol, and dissolve 6-8 mmol of NH4Cl in 30 mL of deionized water. Mix and stir the two solutions for 30-60 min. Transfer the mixed solution to a hydrothermal reactor and react at 160 °C for 12 h. After cooling, wash with ethanol and deionized water by centrifugation and dry to obtain a white powder, which is BiOCl.
[0011] S4. Modify BiOCl and amino carbon nanotubes (NH2CNT) using hexadecyltrimethylammonium bromide (CTAB): prepare 50 mL of 0.1% CTAB aqueous solution, disperse 0.08-0.12 g BiOCl powder in the CTAB solution and ultrasonicate for 30 min to obtain CTAB-modified BiOCl. In addition, disperse 0.08-0.12 g NH2CNT powder in 50 mL CTAB solution and ultrasonicate for 30 min to obtain CTAB-modified NH2CNT.
[0012] S5. Preparation of MXene-based heterojunction structures: Dilute MXene colloid to 0.4-0.6 mg mL -1 , ultrasonically dispersed uniformly, and then a certain amount of CTAB was added to co-modify the BiOCl and NH2CNT composites under the assistance of ultrasound. Then centrifugation and washing were performed to obtain the product MXene-NH2CNT-BiOCl-x.
[0013] Preparation of S6, MXene-NH2CNT-BiOCl-xS: Prepare a mixed solution of 50 mL of deionized water and 10 mL of ethanol. Weigh 0.5-0.6 g of sodium thiosulfate pentahydrate (Na2S2O3·5H2O) and 0.6-0.8 g of sodium sulfide nonahydrate (Na2S·5H2O) and add them to the mixed solution, stir thoroughly to dissolve, then add 0.06-0.12 g of MXene-NH2CNT-BiOCl-x powder and stir evenly. Add 20-21 mL of 1M hydrochloric acid (HCl) solution dropwise under rapid stirring and stir evenly. Add 0.02-0.04 g of polyvinyl pyrrolidone (PVP) and continue stirring for 3 h. Ultrasonicate the stirred solution in an ice water bath for 30 min. After centrifugation and washing with deionized water, the final product MXene-NH2CNT-BiOCl-xS (x = 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3) was obtained.
[0014] Preferably, the temperature of the water bath in step S1 is set to 35°C.
[0015] Preferably, the mass ratio of MXene to NH2CNT in step S5 is 1:1, that is, 0.05-0.06 g NH2CNT is added.
[0016] Preferably, in the MXene-NH2CNT-BiOCl-x in step S5, x=0.1.
[0017] Compared with the existing technology, the present invention provides a method for preparing a MXene sulfur-loaded cathode co-modified with flexible amino carbon nanotubes and BiOCl, which has the following beneficial effects:
[0018] The beneficial effects of the present invention are as follows: the lithium-sulfur battery system has problems such as lithium polysulfide dissolution and shuttle effect, poor conductivity of the positive electrode material, and low cycle efficiency. This paper aims to improve these problems of lithium-sulfur batteries from two aspects: the morphology and catalytic effect of the positive electrode material of the lithium-sulfur battery. The main work and innovations are as follows:
[0019] Few-layer MXene materials with large surface area and good conductivity are used as substrate materials, and NH2CNT is used to support the few-layer MXene to prevent it from stacking. The effects of different proportions of BiOCl on the performance of MXene-NH2CNT-BiOCl-xS cathode materials are explored. In the process of synthesizing materials, only simple CTAB cation modification and ultrasound-assisted synthesis of flexible, self-supporting materials are used.
[0020] The beneficial effects of the present invention are as follows: the surface cation modification of NH2CNT and BiOCl is performed by using surfactant CTAB, so that their surfaces are positively charged. Under the assistance of ultrasound, the positively charged NH2CNT and BiOCl are combined with the negatively charged groups on the surface of the negatively charged MXene through electrostatic adsorption force. CNT can not only increase the conductivity, but also avoid the stacking of MXene. BiOCl is a highly efficient electrocatalyst, and a large number of Bi atoms are exposed on its outer surface. The halogen atoms with strong electronegativity can reduce the electron cloud density on the Bi surface, so that the empty orbit of Bi has abundant active sites, thereby accepting external electrons from polysulfides. Therefore, it has strong chemical adsorption and catalytic ability for polysulfides. The results of electrochemical performance test analysis show that when the mass fraction of BiOCl is 10%, the cycle performance and rate performance of the material are better. Within a certain range, as the mass fraction of BiOCl increases, its adsorption capacity for polysulfides is enhanced, but after increasing to a certain amount, BiOCl with poor conductivity will reduce the overall conductivity of the material, resulting in performance degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of a MXene-NH2CNT-BiOCl-0.1 sulfur-loaded MXene cathode co-modified with flexible amino carbon nanotubes and BiOCl proposed in the present invention;
[0022] Figure 2 This is a TEM image of a MXene-NH2CNT-BiOCl-0.1 sulfur-loaded positive electrode co-modified with a flexible amino carbon nanotube and BiOCl proposed in the present invention;
[0023] Figure 3 This is a battery performance diagram of a flexible amino carbon nanotube and BiOCl co-modified MXene sulfur-loaded cathode MXene-NH2CNT-BiOCl-xS sample proposed in the present invention after 100 cycles at a rate of 0.5C;
[0024] Figure 4 This is a rate performance diagram of a MXene-NH2CNT-BiOCl-xS sample of a MXene-loaded sulfur cathode co-modified with a flexible amino carbon nanotube and BiOCl proposed in the present invention;
[0025] Figure 5 This is the in-situ XRD pattern of the MXene-NH2CNT-BiOCl-0.1-S sample, a MXene-sulfur-loaded cathode co-modified with flexible amino carbon nanotubes and BiOCl, proposed in the present invention; DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0027] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0028] Example 1, a method for preparing a flexible amino carbon nanotube and BiOCl co-modified MXene sulfur-loaded positive electrode, using a few-layer MXene as a base material, using a surfactant cetyltrimethylammonium bromide (CTAB) to perform surface cation modification on NH2CNT and BiOCl, preparing a heterojunction structure material MXene-NH2CNT-BiOCl-x (x=0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3 is the mass fraction of BiOCl) by ultrasound assistance, and then synthesizing MXene-NH2CNT-BiOCl-S by an in-situ sulfur fixation method, the general formula is MXene-NH2CNT-BiOCl-xS (x=0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3), comprising the following steps:
[0029] S1. Preparation of multilayer MXene: Weigh 8-10 g lithium fluoride powder (LiF), dissolve it in 80 mL polytetrafluoroethylene beaker containing 9-10 M hydrochloric acid and stir for 30-60 min. Slowly add 8-10 g MAX (Ti3AlC2) into the polytetrafluoroethylene beaker and stir for 20-24 h. Then centrifuge and wash with deionized water until the pH of the supernatant is >5. The precipitate obtained is multilayer MXene (Ti3C2T x ).
[0030] S2. Preparation of few-layer MXene: Pour a certain amount of anhydrous ethanol into a three-necked flask, pass inert gas for 10-15 minutes, then pour into a centrifuge tube containing multilayer MXene for ultrasonic centrifugation. After the centrifugation, pour out the supernatant. Pour deionized water from which air has been removed into a centrifuge tube containing the precipitate for ultrasonic centrifugation. After the centrifugation, the upper liquid obtained is the few-layer MXene. Use a filter membrane to filter a certain volume of the few-layer MXene, dry it, and weigh it to calculate the concentration of the few-layer MXene colloid.
[0031] S3. Preparation of BiOCl: Dissolve 8-10 mmol of bismuth nitrate pentahydrate (Bi(NO3)2·5H2O) in 10 mL of ethylene glycol, and dissolve 8-10 mmol of NH4Cl in 30 mL of deionized water. Mix and stir the two solutions for 30-60 min. Transfer the mixed solution to a hydrothermal reactor and react at 160 °C for 12 h. After cooling, wash with ethanol and deionized water by centrifugation and dry to obtain a white powder, which is BiOCl.
[0032] S4. Modify BiOCl and amino carbon nanotubes (NH2CNT) using hexadecyltrimethylammonium bromide (CTAB): prepare 50 mL of 0.1% CTAB aqueous solution, disperse 0.08-0.15 g BiOCl powder in the CTAB solution and ultrasonicate for 30 min to obtain CTAB-modified BiOCl. In addition, disperse 0.08-0.15 g NH2CNT powder in 50 mL CTAB solution and ultrasonicate for 30 min to obtain CTAB-modified NH2CNT.
[0033] S5. Preparation of MXene-based heterojunction structures: Dilute MXene colloid to 0.8-1.2 mg mL -1 , ultrasonically dispersed uniformly, and then a certain amount of CTAB-modified BiOCl and CTAB-modified NH2CNT were added under the assistance of ultrasound. Then centrifugation and washing were performed to obtain the product MXene-NH2CNT-BiOCl-x.
[0034] Preparation of S6, MXene-NH2CNT-BiOCl-xS: Prepare a mixed solution of 50 mL of deionized water and 10 mL of ethanol. Weigh 0.6-0.9 g of sodium thiosulfate pentahydrate (Na2S2O3·5H2O) and 0.6-0.8 g of sodium sulfide nonahydrate (Na2S·5H2O) and add them to the mixed solution, stir thoroughly to dissolve, then add 0.1-0.2 g of MXene-NH2CNT-BiOCl-x powder and stir evenly. Add 40-50 mL of 1M hydrochloric acid (HCl) solution dropwise under rapid stirring and stir evenly. Add 0.04-0.05 g of polyvinyl pyrrolidone (PVP) and continue stirring for 3 h. Ultrasonicate the stirred solution in an ice water bath for 30 min. The final product MXene-NH2CNT-BiOCl-xS (x=0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3) was obtained by centrifugation and washing with deionized water. The temperature of the water bath in step S1 was set to 35°C. The mass ratio of MXene to NH2CNT in step S5 was 1:1, i.e., 0.06-0.08g NH2CNT was added. MXene-NH2CNT-BiOCl-x in step S5, x=0.1. ,
[0035] Embodiment 2: This embodiment is based on Embodiment 1, but the difference is that x=0;
[0036] Example 3: This example is based on Example 1, but the difference is that x=0.05;
[0037] Embodiment 4: This embodiment is based on Embodiment 1, but the difference is that x=0.15;
[0038] The following is the preparation of the positive electrode sheet of a lithium-sulfur battery and the preparation of a lithium-sulfur battery using the materials prepared in the examples:
[0039] (1) Preparation of positive electrode sheets for lithium-sulfur batteries:
[0040] Mix MXene-NH2-CNT-BiOCl-xS with conductive carbon black (super p) and binder (polyvinylidene fluoride PVDF) in a mass ratio of 8:1:1, add an appropriate amount of 1-methyl-2-pyrrolidone (NMP), use a shaker to make the material into a slurry, evenly coat the material on aluminum foil, and then dry it in a vacuum oven at 60 ° C overnight. The dried electrode is punched into a circular lithium-sulfur battery positive electrode with a diameter of 12 mm using a slicer.
[0041] (2) Preparation of lithium-sulfur batteries:
[0042] The prepared lithium-sulfur battery positive electrode was used as the working electrode, metallic lithium as the counter electrode, and 1.0 M LiTFSI / 2.0%LiNO3 / DME:DOL=1:1 as the electrolyte, and the button cell was assembled in a glove box with an argon atmosphere (water and oxygen values were both less than 0.1 ppm).
[0043] Figure 1 This is the SEM image of the MXene-NH2CNT-BiOCl-0.1 sample. Under strong electrostatic adsorption, the morphology of the few-layer MXene becomes wrinkled. With the support of NH2CNT, the wrinkled morphology is well maintained. The small square flakes of BiOCl are well embedded in the wrinkled morphology. Figure 2 This is also proved by the TEM images, which shows that MXene, NH2CNT and BiOCl form a good heterojunction structure.
[0044] Figure 3 The battery performance diagram of the MXene-NH2CNT-BiOCl-xS sample after 100 cycles at 0.5C rate. The initial capacity (~990 mAh g -1 ) is significantly higher than the initial capacity when x = 0 (~910 mAh g-1 ), which shows that the addition of BiOCl improves the performance of the battery. After 100 cycles, the capacity of the material with x=0.1 can be maintained at 868 mAh g -1 , above x = 0 (652 mAh g -1 ), x = 0.05 (800 mAh g -1 ), x = 0.15 (742 mAh g -1 ), indicating that adding a certain amount of BiOCl is beneficial to the performance of the battery, but when BiOC exceeds a certain amount, it will occupy the position of sulfur and cannot make the sulfur fully dispersed, resulting in a decrease in the electrochemical performance of the material. Figure 4 The rate performance diagram also illustrates this point.
[0045] Figure 5 This is the in-situ XRD pattern of the MXene-NH2CNT-BiOCl-0.1-S sample of the present invention. The peaks appearing at positions such as 23.1°, 27.8°, and 34.1° are α-S8 peaks. As the discharge proceeds, the electrochemical reaction proceeds to the middle of the first platform, and the S8 peak disappears completely. In the subsequent stage, from the middle of the first platform to the middle of the second platform, the XRD spectrum does not show obvious diffraction peaks other than the background peaks (24.2°, 36°, and 38.5°). After the discharge proceeds to the middle of the second platform, a new diffraction peak appears at 26.7° and 31.2° in the XRD spectrum, which corresponds to the generation of Li2S. Until the end of the discharge, more and more lithium polysulfide is converted into Li2S. As the charging reaction proceeds, Li2S begins to convert into lithium polysulfide, and its diffraction peak gradually weakens. In the middle of the reaction, the Li2S diffraction peak disappears, indicating that almost all Li2S is converted into lithium polysulfide, and there is no obvious lithium polysulfide diffraction peak in the subsequent stage. At the end of the charging stage, new diffraction peaks appeared at positions such as 24.16°, 25.18°, and 28.4° and gradually strengthened. These peaks belonged to γ-S8 because lithium polysulfide tended to generate the lower energy γ-S8 phase.
Claims
1. A method for preparing a MXene sulfur-loaded cathode co-modified with flexible amino carbon nanotubes and BiOCl, characterized in that: Few-layer MXene was used as the substrate material, and the surfactant hexadecyltrimethylammonium bromide (CTAB) was used to perform surface cation modification on amino carbon nanotubes (NH2CNT) and BiOCl. Then, the surface anion-rich MXene was combined with it by an ultrasound-assisted method to prepare flexible, self-supporting and heterojunction-rich MXene-NH2CNT-BiOCl-x (x is the mass fraction of BiOCl; x=0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3) materials. Then, MXene-NH2CNT-BiOCl-S was synthesized by an in-situ sulfur fixation method, and its general formula was MXene-NH2CNT-BiOCl-xS (x=0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3), which specifically included the following steps: S1. Preparation of multilayer MXene: Weigh 2-5 g lithium fluoride powder (LiF), dissolve it in a 20 mL polytetrafluoroethylene beaker containing 9-10 M hydrochloric acid and stir for 30-60 min, slowly add 2-5 g MAX (Ti3AlC2) into the polytetrafluoroethylene beaker and stir for 20-24 h, then centrifuge and wash with deionized water until the pH of the supernatant is >5. The precipitate obtained is multilayer MXene (Ti3C2T x ); S2. Preparation of few-layer MXene: Pour anhydrous ethanol into a three-necked flask, pass inert gas for 10-15 min, then pour into a centrifuge tube containing multilayer MXene and perform ultrasonic centrifugation. After the centrifugation, pour out the supernatant, pour deionized water from which air has been removed into the centrifuge tube containing the precipitate and perform ultrasonic centrifugation. After the centrifugation, the upper layer liquid obtained is the few-layer MXene. Use a filter membrane to filter the few-layer MXene, dry it, and weigh it, so as to calculate the concentration of the few-layer MXene colloid; S3. Preparation of BiOCl: Dissolve 4-5 mmol bismuth nitrate pentahydrate (Bi(NO3)2·5H2O) in 10 mL ethylene glycol, and dissolve 4-5 mmol NH4Cl in 30 mL deionized water. Mix and stir the two solutions for 30-60 min, transfer the mixed solution to a hydrothermal reactor, react at 160 °C for 12 h, cool, wash with ethanol and deionized water, centrifuge, and dry to obtain a white powder, which is BiOCl. S4. Use hexadecyltrimethylammonium bromide (CTAB) to perform surface cation modification on BiOCl and amino carbon nanotubes (NH2CNT): prepare 50 mL of 0.1% CTAB aqueous solution, disperse 0.05-0.1 g BiOCl powder in the CTAB solution and ultrasonicate for 30 min to obtain CTAB-modified BiOCl, disperse 0.05-0.1 g NH2CNT powder in 50 mL CTAB solution and ultrasonicate for 30 min to obtain CTAB-modified NH2CNT; S5. Preparation of MXene-based heterojunction structures: Dilute MXene colloid to 0.4-0.6 mg mL -1 , ultrasonically dispersed uniformly, then added CTAB-modified BiOCl and CTAB-modified NH2CNT under the assistance of ultrasound, and then centrifuged and washed to obtain the product MXene-NH2CNT-BiOCl-x; S6. Preparation of typical MXene-NH2CNT-BiOCl-xS: prepare a mixed solution of 50 mL of deionized water and 10 mL of ethanol, weigh 0.403-0.404 g of sodium thiosulfate pentahydrate (Na2S2O3·5H2O) and 0.499-0.600 g of sodium sulfide nonahydrate (Na2S·5H2O) and add them to the mixed solution, stir thoroughly to dissolve, then add 0.05-0.1 g of MXene-NH2CNT-BiOCl-x powder and stir evenly, while stirring, add 20-21 mL of 1M hydrochloric acid (HCl) solution dropwise and stir evenly, add 0.01-0.02 g of polyvinyl pyrrolidone (PVP) and continue stirring for 3 h, and ultrasonicate the stirred solution in an ice water bath for 30 min and washed by centrifugation with deionized water to obtain the final product MXene-NH2CNT-BiOCl-xS (x = 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3).
2. The method for preparing a MXene sulfur-loaded cathode co-modified with flexible amino carbon nanotubes and BiOCl according to claim 1, characterized in that: The temperature of the water bath in step S1 is set to 35°C.
3. The method for preparing a MXene sulfur-loaded cathode co-modified with flexible amino carbon nanotubes and BiOCl according to claim 1, characterized in that: In step S5, the mass ratio of MXene to NH2CNT is 1:1, that is, 0.05-0.1 g NH2CNT is added.
4. The method for preparing a flexible amino-modified carbon nanotube and BiOCl co-modified MXene sulfur-loaded cathode according to claim 1, characterized in that: MXene-NH2CNT-BiOCl-x (x = 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3) in step S5.
Citation Information
Patent Citations
Porous composite carbon material and production method thereof
JP2014231453A
Materials and methods of use thereof
WO2024076558A1